Sistemas de informação no processo de tomada de decisão na agricultura familiar - Lizzoni, Luciano (2017)
The objectives of this study are to understand the difficulties that the family farmer faces when he decides to diversify his production. Also, analyze the Information Systems available that help the producer in decision making. Finally, elaborate a software project and implement a web application that makes possible the financial planning for a new rural activity. For this purpose, a questionnaire was applied to 20 family farmers of Oeste Paranaense with a quantitative approach, and a bibliographical and documentary research was carried out to verify Information Systems available in the market. Subsequently, a software project was developed using UML elements and ASP.NET Core MVC development framework, with PostgreSQL database. The results show that family farmers have difficulties in the financial planning of a new rural activity and little knowledge about people or entities that offer this service. In addition, all have access to the Internet and wants to improve their knowledge in the rural sector. The implementation of the software project resulted in a web application that assists in decision making when the farmer decides to invest in a new rural activity. Based on financial models pre-registered in the system by agricultural technicians, and a table of inputs with updated prices, the farmer can select a particular model, simulate the production, and check the financial results. It is concluded that family farming is lacking Information Systems for decision making, and the application developed meets the objective proposed in this study, contributing to the decision making of a new rural activity.